2018
DOI: 10.3390/ijms19092493
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miRNA Signatures for Late-Onset Acute Graft-Versus-Host Disease in Allogenic Hematopoietic Stem Cell Transplantation

Abstract: Recent studies have demonstrated that exosomal microRNAs (miRNAs) have the potential of facilitating molecular diagnosis. Currently, little is known about the underlying mechanism behind late-onset acute graft-versus-host disease (LA GVHD). Identifying differentially expressed miRNAs in exosomes should be useful for understanding the role of miRNAs in this disease. This study was established to investigate the relevance of miRNAs in exosomes derived from patients developing LA GVHD after allogeneic hematopoiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…EV fraction was purified with Exoquick-TC regent (System Biosciences) according to the manufacturer's instructions. EVs were quantitated with a nanoparticle tracking analysis (NanoSight LM10; Malven) (16)(17)(18). Isolation of BM-MSC-derived EV-miRs or cellular-miR and serum EV-miR was performed using the miRNeasy kit (Qiagen).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…EV fraction was purified with Exoquick-TC regent (System Biosciences) according to the manufacturer's instructions. EVs were quantitated with a nanoparticle tracking analysis (NanoSight LM10; Malven) (16)(17)(18). Isolation of BM-MSC-derived EV-miRs or cellular-miR and serum EV-miR was performed using the miRNeasy kit (Qiagen).…”
Section: Methodsmentioning
confidence: 99%
“…Screening of candidate miRNA. miRNA profiling was carried out using a TaqMan low-density miRNA array (TLDA; Thermo Fisher Scientific, Inc.), as previously reported (16,17). PCR was done on a Applied Biosystem 7900 HT thermocycler (Carlsberg) according to the manufacturer's recommended program (the reaction was first incubated at 95˚C for 2 min, followed by 50 cycles of 95˚C for 15 sec and 60˚C for 1 min) using SDS2.2 software and Data Assist (Thermo Fisher Sciences, Inc.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomes are lipid‐membrane vesicles which are created by endocytosis and are known as other factors that are involved in the pathogenesis of MM. It is revealed that exosomal miRNA signatures are very important in allogeneic stem cell transplantation . Exosomes are released into the extracellular milieu when the multivesicular bodies (MVBs) joined the plasma membrane .…”
Section: Introductionmentioning
confidence: 99%
“…It is revealed that exosomal miRNA signatures are very important in allogeneic stem cell transplantation. 13 Exosomes are released into the extracellular milieu when the multivesicular bodies (MVBs) joined the plasma membrane. 14 Exosomes secretion, by tumor or normal cells, including epithelial, mast, B, T, and dendritic cells, can be induced or spontaneous, and can take place under pathological and physiological situations.…”
Section: Introductionmentioning
confidence: 99%